Hybriding Technology In Organizational Communications In Government - Vannyora Okditazeini (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
The development of industry 4.0 has blurred the distance between the government and society through hybridization of technology that is applied by the government to support government transformation at the organizational and bureaucratic levels which can improve changes in organizational relations for the better. This can be seen from the new application that is used to become a bridge between the government and its citizens. In addition, the use of technology in the implementation of government performance that is more effective and efficient causes government organizations to be far from being as rigid as what has been attached to organizations so far. This research is a meta-synthesis research with a qualitative meta-aggregation approach. The results of the study show that based on the application of technology in government organizations, hybridization of technology within government organizations requires integration between information technology and social sciences, because technological hybridization is basically an organization that must be regulated.